2010
DOI: 10.1038/nn.2654
|View full text |Cite
|
Sign up to set email alerts
|

The habenula is crucial for experience-dependent modification of fear responses in zebrafish

Abstract: The zebrafish dorsal habenula (dHb) shows conspicuous asymmetry in its connection with the interpeduncular nucleus (IPN) and is equivalent to the mammalian medial habenula. Genetic inactivation of the lateral subnucleus of dHb (dHbL) biased fish towards freezing rather than the normal flight response to a conditioned fear stimulus, suggesting that the dHbL-IPN pathway is important for controlling experience-dependent modification of fear responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
394
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(404 citation statements)
references
References 15 publications
10
394
0
Order By: Relevance
“…Axons of OB output neurons terminate at the medialmost part of the neuropil domain in the rHb, presumably transmitting the odour information to the ventral part of interpeduncular nucleus. Two recent studies in zebrafish have shown that the Hb plays roles in controlling fear responses in experience-dependent manners 45,46 . However, it is tempting to speculate that the OB-rHb pathway may be a part of hard-wired circuits that mediate stereotyped responses such as innate behaviours, because the rHb receives strongly biased projections from particular glomerular clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Axons of OB output neurons terminate at the medialmost part of the neuropil domain in the rHb, presumably transmitting the odour information to the ventral part of interpeduncular nucleus. Two recent studies in zebrafish have shown that the Hb plays roles in controlling fear responses in experience-dependent manners 45,46 . However, it is tempting to speculate that the OB-rHb pathway may be a part of hard-wired circuits that mediate stereotyped responses such as innate behaviours, because the rHb receives strongly biased projections from particular glomerular clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The dHb L -silenced zebrafish show increased freezing in the course of a fear-conditioned assay (26,28), suggesting that this subnucleus is crucial for the modifications of behavior responses in an experience-dependent manner. A very recent study demonstrated that the dHb-interpeduncular nucleus silenced zebrafish exhibits intense innate fear expression, indicating a state of elevated baseline anxiety (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when adult goldfish were trained in a swimming task by pairing a 5 or 15 s light CS with an aversive US (an electrical shock), the fish displayed a response function (water displacement induced by fish activity) with a peak centred around the scheduled time of shock delivery following 200 training trials distributed across 20 sessions [61]. In a different CS-US aversive conditioning task, both adult [62] and larval [63] zebrafish acquired the CS-US contingency (less than 15 s) after about 10 conditioning trials. In this type of conditioning task, accurate timing is required to ensure that responses do not occur too early or too late, but are optimized.…”
Section: (A) Conditioned Swimming Behavioursmentioning
confidence: 99%